(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2021)
Online grocery shopping is a new means of buying preferred grocery products over the Internet for household consumption. The phenomenon has already picked up momentum in the developed countries and an increasing number of urban and sub-urban consumers are utilizing it for their benefit and convenience. The markets in India have also started responding positively to this phenomenon. Slowly but steadily, in almost a decade every Indian metropolitan city has embraced this technology and is now gradually spreading to tier-II and tier-III cities. In the state of Gujarat, the online grocery business practically took off in the year 2012. In cities like Surat, there have been quite a few upcoming companies in this segment at the local level viz. Grabvia.com, Mycitycart.com and Homebethe.com and few others. A few national level players have also entered this city for selling groceries online. This paper attempts to present a study conducted on determining the shopping intentions of consumers towards online grocery products in the city of Surat, Gujarat.